Dari Bounded System ke Borderless Society: Krisis Metode Antropologi dalam Memahami Masyarakat Masa Kini - Irwan Abdullah (Antropologi Indonesia, 2006)
Society and culture can no longer be viewed as they have been in the past. Fundamental changes in group and cultural dynamics provide a new context with implications on how anthropological research must be done. A major change is the shift from the view of societies and cultures as bounded systems to the deterritorialization of culture. The author identifies three stages of change bearing upon agrarian cultures, i.e., market entry, market integration and market expansion. There is a new social reality wherein increasingly intensive mobility is enabled by transportation and communication, thus allowing movement across geographic and cultural boundaries. The author notes that the implications of this are manifold, i.e., a shift in the context for the production of meaning; the problem of the locus of culture; conventional methods of data collection that do not inform the anthropologist on how to handle data available from electronic media; the problem of representation and representativeness; and the matter of determining the unit of analysis in research. Key words: culture change; cultural deterritorialization; research methods.